2021
DOI: 10.7307/ptt.v33i2.3704
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on Public Transportation Usage and Ambient Air Quality in Turkey

Abstract: COVID-19 caused by the SARS-CoV-2 virus is a global health concern due to the quick spread of the disease. In Turkey, the first confirmed COVID-19 case and death occurred on 11 and 15 March 2020, respectively. There is a lack of research on the impact of COVID-19 on public transportation mobility and the Air Quality Index (AQI) around the world. The objective of this research is to consider the impact of COVID-19 on public transportation usage and consequently the AQI level in Turkey. Data collection for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Similar change in travel behaviour and reduction in usage of public transportation have been observed also in other parts of the world. The cities like Istanbul and Ankara in Turkey observed more than 80% reduction in the usage of public transportation (Sahraei et al, 2021b ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Similar change in travel behaviour and reduction in usage of public transportation have been observed also in other parts of the world. The cities like Istanbul and Ankara in Turkey observed more than 80% reduction in the usage of public transportation (Sahraei et al, 2021b ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that public transport ridership has not been shown to increase COVID-19 cases with proper precautionary measures such as social distancing, increased air circulation, mandatory face coverings [92]. However, the uneasiness of shared public spaces during the COVID-19 lockdown resulted in up to an 80-90% decrease in public transport ridership, globally, leading to significant improvements to air quality due to the reduction of public transportation operation [88,93]. The aversion to public transport during COVID-19 has resulted in the increased uptake and encouragement of outdoor, private modes of transport such as bicycling and walking [94].…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences in the impact of the epidemic in various regions cannot be analyzed simply from these factors, as shown in articles published by individual scholars. It can also be comprehensively discussed from factors such as climate factors [33,34], geographical environment [35], traffic factors [36,37] other environmental factors [38], population density [39], block time [40] and regional economic conditions [41]. Of course, when discussing the impact on the tourism industry, in addition to discussing the impact on residents' travel potential, you can also analyze the changes in tourism-related companies such as financial status [42,43] and tourists' consumption behavior [44,45].…”
Section: Discussionmentioning
confidence: 99%